2015
DOI: 10.1371/journal.pone.0125049
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity Rate Prediction of Dengue Hemorrhagic Fever (DHF) Using the Support Vector Machine and the Aedes aegypti Infection Rate in Similar Climates and Geographical Areas

Abstract: BackgroundIn the past few decades, several researchers have proposed highly accurate prediction models that have typically relied on climate parameters. However, climate factors can be unreliable and can lower the effectiveness of prediction when they are applied in locations where climate factors do not differ significantly. The purpose of this study was to improve a dengue surveillance system in areas with similar climate by exploiting the infection rate in the Aedes aegypti mosquito and using the support ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 33 publications
0
37
0
Order By: Relevance
“…In contrast, Kesorn et al [13] observed that only weather variables would not be sufficient for precisely forecasting dengue outbreaks. They introduced "mosquito infection rate" as a new feature, and used six different machinelearning models for comparison in two different scenarios (namely, with vs. without the new feature).…”
Section: Related Workmentioning
confidence: 95%
“…In contrast, Kesorn et al [13] observed that only weather variables would not be sufficient for precisely forecasting dengue outbreaks. They introduced "mosquito infection rate" as a new feature, and used six different machinelearning models for comparison in two different scenarios (namely, with vs. without the new feature).…”
Section: Related Workmentioning
confidence: 95%
“…Applying SVM with the radial basis function (RBF) kernel, scientists were able to forecast the high morbidity rate and take precautions to prevent such cases to happen. The parameter that was able to reach a high level of accuracy was not linked to climate but to the infection rate of the mosquitoes that transmit dengue virus (Kesorn et al, 2015). It most cases of infectious diseases the success transmission blockade is usually linked to outreach (Saybani et al, 2016).…”
Section: Epidemiology and Transmissionmentioning
confidence: 99%
“…There are several time series model methods that can be used to forecast the incidence of infectious diseases and have been widely utilized in this context (Aloufi et al, 2016;Kane et al, 2014;Kesorn et al, 2015;Wu et al, 2017;Zhang et al, 2016Zhang et al, , 2014. Recently, machine learning-based time series models have been effectively used for modelling incidence of infectious disease and forecasting problems in public health studies including support vector machines (SVMs) (Kesorn et al, 2015;Kisi, Parmar, Soni, & Demir, 2017;Zhang et al, 2014), random forest (RF) (Kane et al, 2014;Wu et al, 2017) and multivariate adaptive regression splines (MARSs) (Kisi et al, 2017). These techniques account for the non-linear effects of predictors (which are usually considered as linear in traditional models or where possible there is limitation in the number of non-linear effects in traditional models due to issues such as identifiability) as well as all interactions between predictors which make machine learning methods powerful tools for forecasting.…”
mentioning
confidence: 99%